AN IDEOGRAPHY OF AMERICAN NATIONALISM - GHERASIM, Gabriel C. (Studia Universitatis Babes-Bolyai Studia Europaea, 2020)
The study of American nationalism is a tricky adventure, first because of its deep-seated inconsistency as a self-reliant ideology, and second, because of dispersed and random absorptions of its designations by various and often competing factions and policies. In the first case, it has been said that nationalism could stand as a clarifying description of other self-contained ideologies (e.g., national liberalism); on the other hand, due to its pervasively undetermined ideological contours, any investigation of nationalism results in irresolute paradoxes and baffling contradictions. Still, despite such hindrance, the ideological framing of nationalism might be achieved considering certain valuable traits which hint at its commonsensical profile. In keeping with historical, political and cultural development of nationalism in the United States, one could grasp its certain specific marks as an ideology in the concepts of identity and character, American Creed, Manifest Destiny, assimilationism, American System, messianism. The present study modestly attempts to cope with all the aforementioned traits of American nationalism in order to configure its plausible ideography.